APLIKASI PEMBELAJARAN KISAH TELADAN RASULULLAH MUHAMMAD SAW BERBASIS MULTIMEDIA - I Gede Harsemadi; Riza Wulandari; Akmal Ibnu Rosyadi; I Wayan Gede Lamopia; Dedy Panji Agustino (CENDEKIA: Jurnal Studi Keislaman, 2022)
The advancement of technology has a negative impact on the younger generation, one of which is from the knowledge of moral values that have been taught by the Prophet SAW . This research aims to produce a multimedia - based application of learning the prophet Muhammad's exemplary story that utilizes technology positively so that the younger generation can still follow technological progress without abandoning the teachings of the prophet's exemplary story that has been taught. This application is built by appl ying the MDLC method. Applications are designed using Adobe Illustrator CC 2018, Adobe Animate CC 2018 to create applications with the Actionscript 3.0 programming language, and Adobe Audition CC 2018 to process audio data. The result of making this applic ation, which is an application that contains the story of the Prophet Muhammad (peace be upon him) is presented with an interesting look that includes multimedia elements in it.